2019
DOI: 10.1002/pd.5528
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of a novel automated cell‐free DNA screening assay for trisomies 21, 13, and 18 in maternal plasma

Abstract: ObjectiveTo evaluate clinical performance of a new automated cell‐free (cf)DNA assay in maternal plasma screening for trisomies 21, 18, and 13, and to determine fetal sex.MethodMaternal plasma samples from 1200 singleton pregnancies were analyzed with a new non–sequencing cfDNA method, which is based on imaging and counting specific chromosome targets. Reference outcomes were determined by either cytogenetic testing, of amniotic fluid or chorionic villi, or clinical examination of neonates.ResultsThe samples e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 15 publications
0
34
1
1
Order By: Relevance
“…The first pass failure rate of 1.5% in this study was higher than what has previously been reported for this technology, 6 , 7 but still significantly lower than most other technologies and is comparable to that of massive parallel sequencing‐based NIPT methods, which showed the lowest average failure rate based on a meta‐analysis of NIPT failure rates. 2 By also employing a repeat‐testing approach with this technology, the effective failure rate in this study was reduced by 87% to 0.2%.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The first pass failure rate of 1.5% in this study was higher than what has previously been reported for this technology, 6 , 7 but still significantly lower than most other technologies and is comparable to that of massive parallel sequencing‐based NIPT methods, which showed the lowest average failure rate based on a meta‐analysis of NIPT failure rates. 2 By also employing a repeat‐testing approach with this technology, the effective failure rate in this study was reduced by 87% to 0.2%.…”
Section: Discussioncontrasting
confidence: 48%
“…The Vanadis NIPT test used in this study has previously been validated with a low failure rate on a high‐risk population. 6 The present study was carried out to evaluate test performance in a general‐risk population. In addition, a screening strategy to reduce the test failure rate through repeat testing was evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Vanadis ® NIPT is a new technology targeting relevant chromosomes, based on digital molecular quantification in a 96-well microplate [7,8]. The method converts targeted chromosomal fragments into digitally quantifiable objects through rolling-circle replication and chromosome-specific labeling.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, regarding the detection of autosomal trisomies (involving chromosomes 21, 18 and 13), low-cost methods are being developed, such as selectively amplifying only a specific region of the target chromosome and analyzing it using microarrays, 49 quantitative PCR analysis and selectively coloring and quantifying only a specific region of the target chromosome. 50 Furthermore, tests for detecting monogenic diseases have also been clinically applied, and the number of target diseases is increasing.…”
Section: Discussionmentioning
confidence: 99%